1990
DOI: 10.1029/wr026i010p02339
|View full text |Cite
|
Sign up to set email alerts
|

Apparent dispersion in transient groundwater flow

Abstract: This paper investigates the effects of large‐scale temporal velocity fluctuations, particularly changes in the direction of flow, on solute spreading in a two‐dimensional aquifer. Relations for apparent longitudinal and transverse dispersivity are developed through an analytical solution for dispersion in a fluctuating, quasi‐steady uniform flow field, in which storativity is zero. For transient flow, spatial moments are evaluated from numerical solutions. Ignored or unknown transients in the direction of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 7 publications
2
69
1
Order By: Relevance
“…The scale dependence of dispersivity is generally believed to result from spatial and temporal variations in the ground-water velocity field, which are caused by both spatial variations in hydraulic conductivity, and spatial and temporal variations in hydraulic gradient (Goode and Konikow 1990). Aquifer heterogeneity results in additional plume dispersion, beyond that seen in the laboratory, because the solute moves at different rates through different parts of the aquifer.…”
Section: Dispersivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The scale dependence of dispersivity is generally believed to result from spatial and temporal variations in the ground-water velocity field, which are caused by both spatial variations in hydraulic conductivity, and spatial and temporal variations in hydraulic gradient (Goode and Konikow 1990). Aquifer heterogeneity results in additional plume dispersion, beyond that seen in the laboratory, because the solute moves at different rates through different parts of the aquifer.…”
Section: Dispersivitymentioning
confidence: 99%
“…Aquifer heterogeneity results in additional plume dispersion, beyond that seen in the laboratory, because the solute moves at different rates through different parts of the aquifer. Temporal variations in hydraulic gradient have been shown to have a strong effect on transverse dispersion (Goode and Konikow 1990;Rehfeldt and Gelhar 1992;van der Kamp et al 1994). …”
Section: Dispersivitymentioning
confidence: 99%
“…Several researchers Goode and Konikow, 1990;Dagan et al, 1996) identified slowly varying, unsteady, uniform flow characterized by variation in the direction of the hydraulic gradient as a possible explanation for the observed transverse macrodispersivities being larger than predicted by the steady-state theory. This mechanism allows the plume to slowly shift from side to side.…”
Section: -14mentioning
confidence: 99%
“…For example, Sugita and Gillham (1995a,b) present a conceptual model that indicates a nonideal reactive breakthrough (i.e., greater spreading and tailing) greater than predictable by the classical advectivedispersion equation with pore scale variations in retardation factor. Goode and Konikow (1990) illustrate that uncertainty in transient flow behavior gives rise to a greater apparent dispersivity. Tritscher et al (2000) illustrate that neglecting unsaturated zone effects leads to a local specific yield strongly influenced by water table depth and mildly dependent on recharge rate.…”
Section: Process Identification Simplification and Representationmentioning
confidence: 99%